Enhancing counseling teachers’ creativity through Deep Counseling-based Training - Eka Sakti Yudha; Ahman; Agus Taufiq; Dian Munawarah; Kania Cahyaningtyas; Moch. Dendi Arief Prawira; Muzayyinah Al-Usrah; Yalda Suvita (University of Merdeka Malang, 2025)
This community service program aimed to enhance the creativity of guidance and counseling teachers through deep counseling-based training. The training was conducted on July 10, 2025, involving 49 guidance and counseling teachers from junior and senior high schools. Using the Participatory Action Research (PAR) method, the program included pre-test, panel discussion on deep counseling, innovation showcase, practical sessions, and post-test. Results showed a positive impact on teachers' creativity, with participants in the